Immobilised semiconductors for photocatalytic water purification - Odling, Gylen (The University of Edinburgh, 2019)
TiO2 based nanomaterials are currently the most widely studied for photocatalytic water purification. Despite high stability and low environmental impact, instances of water treatment applications using TiO2 photocatalysis are few due to modest activity only under high energy ultraviolet light. Another drawback is the nanoscale nature of such materials, posing a problem in the separation and re-use of the photocatalytic material. This work aims to overcome these problems by forming nanocomposites between TiO2 and other semiconductors with favourable properties such as visible light harvesting or improved charge separation, and to generate these materials immobilised upon macroscopic supports. Composites of bismuth titanate (BTO) and lanthanum vanadate (LVO) on TiO2 have been prepared immobilised on glass beads using a sequential ionic layer adsorption (SILAR) method. Modification of TiO2 with these wide band gap semiconductors gives little to no extension of the TiO2 absorption into the visible but allows for charge separation between the two materials due to off-set band energies. This improved charge separation and, in the case of BTO-TiO2, modest absorption extension is demonstrated to be effective for the photocatalytic degradation of a variety of different chemical pollutants and bacteria in water. An extensive photocatalytic scope using these materials is presented, in addition to re-use tests and mechanistic investigations. Attempts were made to narrow the band gap and as such harvest a greater portion of visible light by forming composites of BiOI and BiVO4 with TiO2 on glass slides using SILAR. Through electronic and optical characterisation methods these materials were shown to have both the off-set band alignment of the BTO and LVO composites, but with a narrower band gap. Using visible only light the BiOI and BiVO4 materials were applied to the degradation of dyes successfully, however only BiOI was found to have any activity against colourless 4CP. This difference was investigated using comparisons to a ZrO2 model system and was determined to arise from a sensitisation effect of the dye pollutant used. The use of two separate modifications to impart the charge separation and visible light harvesting was investigated. Chlorine doped TiO2 particles were deposited on the TiO2 surface, giving a visible active composite. It was found that this could be improved by the addition of a carbon coating process, allowing photogenerated charges to rapidly move apart and react. This composite was found to be highly stable, particularly under acidic conditions in contrast to the other materials developed. As such its activity was not only tested against the typical organic pollutants, but also for the photocatalytic reduction of Cr(VI) to Cr(III) under acidic conditions.
Keywords: titanium dioxide; TiO2; TiO2 photocatalysis; photocatalytic degradation; immobilised semiconductors